Applying the PBL Method in Science Learning Using PPT and Video Media to Improve Student Ability - Suryati, Cicih; Aulia, Diva; Febrianti, Fira (Jurnal Primagraha, 2022)
This study aims to improve: social studies learning activities through the application of problem-based learning (PBL) assisted by PowerPoint, and social studies learning outcomes for SD NEGERI RAWU students in Serang City. This type of research is classroom action research. The research subjects were students of class IV B of SD NEGERI RAWU City of Serang. The type of action applied is learning with the PBL approach assisted by PowerPoint and videos. Data collection techniques used are documentation, observation, interviews. Data were analyzed with descriptive statistics. This analysis is to explain the development of the learning process and learning outcomes before and after implementing learning with PBL. The results of this study indicate that after carrying out learning actions by applying Powerpoint and video-assisted PBL: 1) there was an increase in learning activities by 57% in cycle I, and 5% in cycle II; 2) there was an increase in learning outcomes of 57.58% in cycle I, and 6.06% in cycle II; 3) there was an increase in learning completeness of 36.37% in cycle I, and 12.12% in cycle II; and 4) increased attitudes and skills of group cooperation by 24.24% in cycle II.